Intrinsic magnetic properties of BixCo2-xMnO 4 spinels obtained by short-time etching - Dos Santos, M. E. [UNESP]; Lisboa Filho, Paulo Noronha [UNESP]; Gouttefangeas, F.; Peña, O. (Elsevier, 2013)
We report the structural and magnetic properties of Co2MnO 4, partially substituted by Bi at the octahedral site. Bismuth enhances ferromagnetism due to a decrease of the Co2+-Co2+ antiferromagnetic interactions and an increase of the Mn3+-Mn 4+ exchanges. Spurious phases (magnetic and/or nonmagnetic oxides) can easily form because of the large differences between the ionic radii of Bi3+ and Co3+, hiding or altering the intrinsic physical properties of the main BixCo2-xMnO4 phase. An easy way to eliminate the secondary phases is using acid reagents. Short-time etching of Bi0.1Co1.9MnO4 using nitric acid was successfully used, keeping most of the properties of the initial compound, with no alteration of the crystallographic structure. Final stoichiometry was respected (∼Bi0.08Co1.82MnO4), meaning that the material after etching definitely contains bismuth elements in its structure and the observed properties are intrinsic to the oxide spinel. Additional experiments were performed as a function of the synthesis conditions, showing that an optimal pH value of 7 allowed the best magnetic response of the non-doped material. © 2013 Elsevier B.V. All rights reserved.
Keywords: Etching; Ferrimagnetism; Multiferroics; Oxide spinel; pH; Additional experiments; Antiferro-magnetic interactions; Crystallographic structure; Magnetic response; Oxide spinels; Structural and magnetic properties; Synthesis conditions; Bismuth; Bismuth compounds; Carbon dioxide; Magnetic properties; Manganese; Manganese oxide; Stoichiometry; Cobalt compounds